Natural disasters, local bank market share, and economic recovery - Justin Gallagher; Daniel Hartley (Federal Reserve Bank of Chicago, 2024)
US Interstate bank deregulation during the 1980s and 1990s led to larger, nationally diversified banks, and a decline in the number of local community banks. Economic theory suggests that community banks may have a greater incentive, but a lower capacity, to lend to a region following a destructive event such as a natural disaster. We test whether there are differences in post-disaster credit allocation and regional redevelopment based on the concentration of local banking at the time of an economic shock. We find causal evidence of less credit allocated and somewhat weaker redevelopment in regions with more local banking.
Keywords: G21; O16; Q54; R11; 330; banking; deregulation; natural disasters